Isolation and identification of endophytic bacteria from Mangifera indica (MANGO) as a potential biocontrol agent against the emerging bacteria causing bacterial blight - Bombales, Hannah Avril; Pomar, Jessica Mae; Valencia, Sophia; Atole-Nieva, Liezel (Academia Journal of Biology, 2025)
Mango (Mangifera indica), the national fruit of the Philippines and an economically important crop, faces various challenges, including diseases such as bacterial blight, which has impacted its production in recent years. This study isolated and identified bacterial endophytes from mango plants and evaluated their antagonistic activity against the emerging bacteria causing bacterial blight pathogen Enterobacter asburiae. A total of thirty-three bacterial isolates were obtained and characterized morphologically and biochemically. Antagonistic assays demonstrated that four isolates inhibited the growth of E. asburiae. 16S rRNA sequencing identified these isolates as members of the genera Bacillus, Alcaligenes, Proteus, Paenibacillus. Among them, isolate CTL S2-R1 (Alcaligenes sp.) exhibited the most significant inhibitory effect, with a mean zone of inhibition of 16.67 ± 1.53 mm. Further investigations are recommended to characterize and identify the antibacterial compounds produced by these endophytes.